Optimization of conservation agriculture and N nutrition in maize–wheat cropping system: assessment on productivity, energy indicator, nutrient apparent balance and economics - CHOUDHARY, R. L.; BEHERA, U. K. (Journal of Soil and Water Conservation, 2021)
A study on agronomic assessment of maize (Zea mays L.)–wheat (Triticum aestivum L.) cropping system (MWCS) under conservation agriculture (CA) and fertilizer-nitrogen (N) management practices was conducted at ICAR-Indian Agricultural Research Institute (IARI), New Delhi. Field experiments were conducted for two consecutive years with six main-plot treatments of tillage and crop-establishment techniques, i.e. conventional-tillage flat-bed (CTF), CT raised-bed (CTB), zero-tillage flat-bed with cropresidues (ZTFR) and without crop-residues (ZTF), ZT raised-bed (permanent bed) with crop-residues (ZTBR) and without crop-residues (ZTB), and four sub-plot treatments of N, i.e. 0, 60, 120 and 180 kg N ha-1 in a fixed layout of split-plot design with three replications. Results revealed that ZTB-based MWCS reduced the cost of cultivation and input energy consumptions by 15.1 and 20.6%, respectively over the CT-based systems. However, recycling of crop-residues under ZT practices (ZTBR/ZTFR) increased these parameters substantially but also resulted the maximum values of the system productivity (8.44 t ha-1), gross output energy (241.3 × 103 MJ ha-1) and gross returns (102.54 × 103 ` ha-1), and improved the N, P and K uptake up to their maximum values, i.e. 188, 32 and 220 kg ha-1, respectively. CA practices (ZTBR/ ZTFR) also found to build the net positive apparent balance of N and P, and reduced the net negative apparent balance of K in soil, which could be helpful in reducing the external fertilizer use in the longrun. Nevertheless, ZTB registered the maximum values of the energy-use efficiency (EUE, 14.75), B:C ratio (2.22) and economic efficiency (248 ` ha-1 day-1) in MWCS. The productivity, nutrient uptake, profitability and energy productions of MWCS significantly improved with 120 kg N ha-1, though higher N rates decreased the EUE significantly. Considering all the parameters, the study recommends that permanent raised-bed system optimally supplemented with N (120 kg N ha-1) is energy efficient and economically most profitable that could be adopted with surface retention of crop-residues by the farmers of IGPs for improving productivity with better quality and soil health and to reduce external-use of fertilizers in the MWCS.